Catalytic efficiency and stability of cobalt hydroxide for decomposition of ozone and p-chloronitrobenzene in water - Xu, Z.; Chen, Z.; Joll, Cynthia; Ben, Y.; Shen, J.; Tao, H. (Elsevier Science, 2009)
Cobalt hydroxide, a stable and efficient catalyst prepared in the laboratory, has been successfully used in the decomposition of ozone and trace quantities of p-chloronitrobenzene (pCNB) in water. The cobalt hydroxide was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and the Brunauer-Emmet-Teller (BET) method. The decomposition rate of aqueous ozone was increased by 1.527 times in the presence of cobalt hydroxide. Increasing the catalyst loading from 0 to 500 mg/L increased the removal efficiency of pCNB from 59% to 99%. The catalyst morphology and its composition were found to be unaltered after the catalytic reaction. After five successive recycles, the catalyst remained stable in the catalytic ozonation of pCNB.